Investigating the mechanism of action of Aristea ecklonii’s suspected antipyretic properties - Muller, Miles Christopher (University of the Witwatersrand, Johannesburg, 2024)
Aristea ecklonii (A. ecklonii) (Baker) is an indigenous, evergreen perennial medicinal plant used amongst South Africans to treat fever. This study aimed to investigate the antipyretic properties of aqueous A. ecklonii root extracts. Male Sprague-Dawley rats (250 – 300 g) received a subcutaneous (s.c.) injection of zymosan (300 mg/kg) or saline before receiving an intraperitoneal injection (i.p.) of paracetamol (50 mg/kg), aqueous A. ecklonii root extract (55 mg/kg) or saline. The i.p. injection was administered 15 h after the s.c. injection. Abdominal temperature was measured using temperature sensitive radio-transmitters. Blood, cerebrospinal fluid (CSF) and hypothalamic tissue was collected 90 min after the i.p. injection for the measurement of cytokines, prostaglandin E2 (PGE2) and enzymes involved in PGE2 synthesis. Zymosan increased abdominal temperature which peaked at 39.42 ± 0.14 °C. Compared to rats that received saline, rats receiving zymosan had increased concentrations of blood plasma IL- 1β and IL-6, increased PGE2 in the CSF and increased hypothalamic expression of COX-2 and mPGES1 (P < 0.05). Paracetamol and aqueous A. ecklonii root extract reduced the zymosan- induced fevers. Rats that received saline, followed by an i.p. injection of aqueous A. ecklonii root extract, had a decrease in abdominal temperature and an increase in blood plasma IL-1β, IL-6, TNF-α and IL-10 concentrations compared to rats that received saline (P < 0.05). Thus, the antipyretic properties of the A. ecklonii root extract seems to be related to its ability to induce systemic inflammation and not reduce the synthesis of hypothalamic PGE2 and thus should be used with caution in ill individuals.
A research report submitted in fulfillment of the requirements for the Master of Science in Medicine, in the Faculty of Health Sciences, School of Physiology, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Fever; phytomedicine; A. ecklonii; zymosan; paracetamol; anti-pyretic; inflammation; hypothermia; rats; cytokine; vasodilation; core temperature; SDG-3: Good health and well-being